Negative electrode material, negative electrode sheet of lithium ion battery and preparation method thereof
By using surfactant to coat graphite in the negative electrode material of lithium-ion batteries and combining phosphorylated chitosan, the problem of the cycling performance of lithium-ion batteries is affected by volume expansion stress, and higher cycling performance and stability are achieved.
Patent Information
- Application Number
- CN201510076746.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2015-02-12
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2035-02-12
AI Technical Summary
The cycling performance of existing lithium-ion batteries is affected by the stress caused by the volume expansion of the negative electrode active substance when embedded in lithium, and it is difficult to achieve substantial breakthroughs in improving the bonding strength of the adhesive.
Graphite, carbon black conductive agent and phosphorylated chitosan are used as negative electrode materials to coat graphite with surfactants, and hydrogen bonds are formed with surfactants on the surface of graphite by using amino groups, hydroxyl groups and other groups of phosphorylated chitosan to form hydrogen bonds with surfactants on the surface of graphite to enhance adsorption force to resist stress caused by volume expansion.
It effectively improves the circulation performance and cycle stability of lithium-ion batteries, reduces the occurrence of graphite layer separation, enhances the adhesion between the negative electrode material and the copper foil, and avoids powder loss.
Smart Images

Figure CN105990580B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium-ion batteries, and in particular to a negative electrode material, a negative electrode sheet for a lithium-ion battery, and a preparation method thereof. Background Art
[0002] Lithium-ion batteries, with their advantages of high energy density, high operating voltage, long cycle life, low self-discharge, no memory effect, and excellent safety, have broad application prospects and have experienced rapid development. However, the rapid development of electronic products and electric vehicles has placed stricter requirements on lithium-ion batteries, including improvements in discharge capacity, safety, high- and low-temperature performance, and cycle performance. Currently, most commercial lithium-ion batteries use lithium cobalt oxide as the positive electrode active material and graphite as the negative electrode active material. The actual specific capacity of electrode materials is increasingly approaching their theoretical specific capacity. Limited by the theoretical lithium storage capacity of electrode materials, it has become difficult to achieve breakthroughs in improving battery performance by improving battery manufacturing technology.
[0003] In order to improve the performance of lithium-ion batteries, people have proposed many solutions starting from the positive and negative electrode materials of the battery, including the development of negative electrode materials with high capacity and improved cycle performance.
[0004] In negative electrode materials, the stress caused by the volume expansion of negative electrode active materials during lithium insertion is an important factor affecting the cycle performance of lithium-ion batteries. The solution has always focused on improving the bonding strength of the binder. At present, research on improving the binder to alleviate the expansion of active materials during lithium insertion has become mature, and it is difficult to achieve substantial breakthroughs. Summary of the Invention
[0005] Based on this, it is necessary to provide a negative electrode material and a preparation method thereof that can improve the cycle performance of a lithium ion battery, and also provide a lithium ion battery negative electrode sheet using such a negative electrode material.
[0006] A negative electrode material comprises graphite, a carbon black conductive agent and phosphorylated chitosan, wherein the graphite is coated with a surfactant, and the mass ratio of the surfactant-coated graphite, the carbon black conductive agent and the phosphorylated chitosan is 8:1:1.
[0007] In one embodiment, the surfactant is selected from one of sodium dodecylbenzenesulfonate, cetyltrimethylammonium bromide and sodium lauryl sulfate.
[0008] A lithium ion battery negative electrode sheet comprises a copper foil and the above-mentioned negative electrode material coated on the surface of the copper foil.
[0009] A method for preparing a negative electrode sheet for a lithium-ion battery comprises the following steps:
[0010] coating graphite with a surfactant;
[0011] The surfactant-coated graphite, carbon black conductive agent, and phosphorylated chitosan were mixed in a mass ratio of 8:1:1 and then stirred with water to prepare a negative electrode slurry; and
[0012] The negative electrode slurry is applied to the surface of the copper foil and dried.
[0013] In one embodiment, the step of coating graphite with a surfactant is specifically as follows:
[0014] An aqueous solution containing 0.2 wt% of a surfactant was mixed with anhydrous ethanol at a volume ratio of 9:1 to form a mixed solution;
[0015] Graphite is placed in the mixed solution and stirred for 60 to 120 minutes, filtered, and dried.
[0016] In one embodiment, before adding the graphite into the mixed solution, the process further includes the step of ball milling the graphite for 12 to 13 hours.
[0017] In one embodiment, phosphorylated chitosan is prepared according to the following steps:
[0018] Chitosan was dissolved in methanesulfonic acid, P2O5 was gradually added at 10-15°C and stirred for 1 hour to prepare a reaction solution;
[0019] Ether was added to the reaction solution to generate a precipitate;
[0020] The precipitate is washed and dried to obtain phosphorylated chitosan.
[0021] In one embodiment, the mass ratio of chitosan to P2O5 is 1:2-3, and the solid-liquid ratio of chitosan to methanesulfonic acid is 1 g:7 ml.
[0022] In the aforementioned negative electrode material, the graphite surface is coated with a surfactant. The amino and hydroxyl groups contained in the phosphorylated chitosan can form hydrogen bonds with the lone pairs of electrons of the surfactant on the graphite surface, generating a strong adsorption force. This can be used to resist the stress caused by the volume expansion of the graphite during lithium insertion, reduce the delamination of the graphite caused by the expansion, and thus improve the cycle capacity of the lithium-ion battery.
[0023] In the above-mentioned lithium-ion battery negative electrode sheet, phosphorylated chitosan is uniformly dispersed in the negative electrode material as a binder, and the negative electrode material is also uniformly adhered to the copper foil. Therefore, the bonding force between the negative electrode material and the copper foil is increased, effectively solving the problem of graphite powder loss caused by stress generated by the expansion of graphite during lithium insertion. Such a lithium-ion battery negative electrode sheet can improve the cycle performance and cycle stability of the lithium-ion battery.
[0024] The above-mentioned method for preparing the negative electrode sheet of a lithium-ion battery has a simple process and mild preparation conditions and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of the preparation process of a negative electrode sheet for a lithium-ion battery according to one embodiment of the present invention;
[0026] Figure 2 This is a comparison chart of the test results of the lithium-ion batteries prepared in Example 3 of the present invention and Comparative Example 1 at a current density of 0.1C;
[0027] Figure 3 This is a comparison chart of the test results of the lithium-ion batteries prepared in Example 4 of the present invention and Comparative Example 2 at a current density of 0.1C;
[0028] Figure 4 This is a comparison chart of the test results of lithium-ion batteries prepared in Examples 5, 6, and 7 of the present invention at a current density of 0.1C;
[0029] Figure 5 This is a comparison chart of the test results of the lithium-ion batteries prepared in Example 8 of the present invention and Comparative Example 2 at current densities of 0.1C, 0.2C, 0.5C, 1C, and 5C, respectively. DETAILED DESCRIPTION
[0030] To facilitate understanding of the present invention, the present invention will be described more fully below with reference to specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, the purpose of providing these embodiments is to provide a more thorough and comprehensive understanding of the disclosure of the present invention.
[0031] The negative electrode material of one embodiment includes graphite, a carbon black conductive agent, and phosphorylated chitosan. The graphite is coated with a surfactant. The mass ratio of the surfactant-coated graphite, the carbon black conductive agent, and the phosphorylated chitosan is 8:1:1.
[0032] Furthermore, the graphite is selected from natural graphite or artificial graphite.
[0033] Furthermore, the carbon black conductive agent is selected from one of surperP and acetylene black (AB).
[0034] Furthermore, the surfactant is selected from one of sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium bromide and sodium lauryl sulfate.
[0035] Among the above-mentioned negative electrode materials, phosphorylated chitosan, as a binder, has good bonding properties and also serves to increase the discharge capacity of the lithium-ion battery and improve the cycle stability.
[0036] Secondly, the graphite is coated with surfactants. These surfactants are anionic surfactants, which form a large number of multi-electron groups on the graphite surface. The amino, hydroxyl and other groups in the phosphorylated chitosan structure can easily form strong hydrogen bond adsorption with the multi-electron groups on the graphite surface, bonding the graphite particles, so that the phosphorylated chitosan coated on the graphite surface can better resist the stress caused by the volume expansion of the graphite when lithium is inserted. The combination of the surfactant-coated graphite and the phosphorylated chitosan further improves the cycle performance of the battery.
[0037] In addition, phosphorylated chitosan is insoluble in the electrolyte commonly used in lithium-ion batteries, and phosphorylated chitosan contains lone pairs of electrons, which play a role in adsorbing lithium ions in the negative electrode material and further promote the formation of SEI film and the stability of SEI film during the cycle.
[0038] Therefore, by cleverly combining surfactant-coated graphite and phosphorylated chitosan, the cycle performance of lithium-ion batteries can be significantly improved. This combination of ideas is even more important in dealing with the problem of expansion of negative electrode active materials in the future.
[0039] A lithium ion battery negative electrode sheet comprises a copper foil and the above-mentioned negative electrode material coated on the surface of the copper foil.
[0040] The thickness of the copper foil and the negative electrode material coated on the surface of the copper foil can be set as needed. Preferably, the thickness of the copper foil is 15 microns.
[0041] In the above-mentioned lithium-ion battery negative electrode sheet, phosphorylated chitosan is uniformly dispersed in the negative electrode material as a binder, and the negative electrode material is also uniformly adhered to the copper foil. Therefore, the bonding force between the negative electrode material and the copper foil is increased, effectively solving the problem of graphite powder loss caused by stress generated by the expansion of graphite during lithium insertion. Such a lithium-ion battery negative electrode sheet can improve the cycle performance and cycle stability of the lithium-ion battery.
[0042] See also Figure 1 A method for preparing a negative electrode sheet for a lithium-ion battery comprises the following steps:
[0043] S10. Coating the graphite with a surfactant.
[0044] In this embodiment, the surfactant coating of graphite includes the following steps:
[0045] S110, mixing an aqueous solution containing 0.2 wt % of a surfactant with ethanol at a volume ratio of 9:1 to form a mixed solution.
[0046] Furthermore, the ethanol is anhydrous ethanol.
[0047] Furthermore, the surfactant is selected from at least one of sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium bromide and sodium lauryl sulfate.
[0048] S130. Ball mill the graphite at a speed of 200-300 r / min for 12-18 hours.
[0049] It is understood that ball milling is to obtain graphite particles with relatively uniform size, and graphite particles can be obtained through other means, so this step can be omitted.
[0050] S150, adding graphite to the mixed solution, stirring for 60 to 120 minutes, filtering, and drying.
[0051] Furthermore, the drying is carried out at 60° C. for 12 hours. Of course, other drying methods can also be used.
[0052] S20. Prepare phosphorylated chitosan.
[0053] In this embodiment, the preparation of phosphorylated chitosan comprises the following steps:
[0054] S210. Dissolve chitosan in methanesulfonic acid, gradually add P2O5 at 10-15°C and stir for 1 hour to obtain a reaction solution.
[0055] Furthermore, the solid-liquid ratio of chitosan and methanesulfonic acid is 1 g:7 ml.
[0056] Furthermore, the mass ratio of chitosan to P2O5 is 1:2-3.
[0057] S230. Add excess ether to the reaction solution to generate a precipitate.
[0058] S250, washing the precipitate, and drying it to obtain phosphorylated chitosan.
[0059] Furthermore, the washing step specifically involves washing with ether, acetone, and methanol in sequence and cycling the washing process multiple times.
[0060] Furthermore, vacuum drying was performed at 37°C.
[0061] It is understandable that steps S10 and S20 do not need to be performed in the order described above, and step S20 may be performed first or simultaneously with step S10.
[0062] S30, mixing the graphite coated with the surfactant, the carbon black conductive agent, and the phosphorylated chitosan in a mass ratio of 8:1:1 and stirring with water to prepare a negative electrode slurry.
[0063] The amount of water here is adjusted according to the required thickness of the negative electrode slurry and there is no special requirement as long as it can be coated.
[0064] S40, coating the negative electrode slurry on the surface of the copper foil and drying.
[0065] The above-mentioned method for preparing the negative electrode sheet of a lithium-ion battery has a simple process and mild preparation conditions and is suitable for industrial production.
[0066] The above-mentioned negative electrode materials are described in detail below with reference to specific embodiments.
[0067] Example 1
[0068] In this embodiment, the specific steps of preparing phosphorylated chitosan are as follows:
[0069] 1 g of chitosan was dissolved in 7 ml of methanesulfonic acid, and 2 g of P2O5 was gradually added at a reaction temperature of 10°C and stirred for 1 hour to prepare a reaction solution.
[0070] Excessive ether was added to the reaction solution to generate a precipitate, which was collected by filtration and washed with ether, acetone, and methanol in a cycle for several times, filtered, and dried in a vacuum at 37° C. to obtain phosphorylated chitosan for use.
[0071] In this embodiment, the specific steps of coating graphite with surfactant are as follows:
[0072] The graphite was ball milled for 12 h with the rotation speed controlled at 200 r / min.
[0073] An aqueous solution containing 0.2 wt% of sodium dodecylbenzenesulfonate (hereinafter referred to as LAS) was mixed with ethanol in a volume ratio of 9:1 to form a mixed solution. Ball-milled graphite particles were added while stirring. After stirring for 60 minutes, the graphite was filtered out and dried to obtain surfactant-coated graphite.
[0074] In the following text, graphite with surface pretreatment is referred to as “graphite@LAS”, and graphite without surface pretreatment is not referred to in particular.
[0075] The negative electrode material includes graphite@LAS, a carbon black conductive agent and phosphorylated chitosan, and the mass ratio of graphite@LAS, the carbon black conductive agent and the phosphorylated chitosan is 8:1:1.
[0076] In this embodiment, the carbon black conductive agent is surperP.
[0077] Example 2
[0078] The negative electrode material includes natural graphite, carbon black conductive agent and phosphorylated chitosan. The graphite is coated with a surfactant. The mass ratio of the surfactant-coated graphite, carbon black conductive agent and phosphorylated chitosan is 8:1:1.
[0079] In this embodiment, the carbon black conductive agent is acetylene black.
[0080] In this embodiment, the specific steps of preparing phosphorylated chitosan are as follows:
[0081] 1 g of chitosan was dissolved in 7 ml of methanesulfonic acid, and 3 g of P2O5 was gradually added at a reaction temperature of 15°C and stirred for 1 hour to prepare a reaction solution.
[0082] Excessive ether was added to the reaction solution to generate a precipitate, which was collected by filtration and washed with ether, acetone, and methanol in a cycle for several times, filtered, and dried in a vacuum at 37° C. to obtain phosphorylated chitosan for use.
[0083] In this embodiment, the specific steps of coating graphite with surfactant are as follows:
[0084] The graphite was ball milled for 13 h with the rotation speed controlled at 200 r / min.
[0085] An aqueous solution containing 0.2 wt % of hexadecyltrimethylammonium bromide and ethanol were mixed at a volume ratio of 9:1 to form a mixed solution, ball-milled graphite particles were added while stirring, and the mixture was further stirred for 120 minutes. After that, the graphite was filtered out and dried to obtain surfactant-coated graphite.
[0086] Sodium carboxymethyl cellulose / Styrene butadiene rubberSodium carboxymethyl cellulose / Styrene butadiene rubberSodium carboxymethyl cellulose / Styrene butadiene rubber
[0087] The performance tests of the negative electrode material and the negative electrode sheet of the lithium ion battery of the present invention are carried out as follows.
[0088] Preparation
[0089] Preparation of phosphorylated chitosan:
[0090] 1 g of chitosan was dissolved in 7 ml of methanesulfonic acid, and 2.3 g of P2O5 was gradually added at a reaction temperature of 13°C and stirred for 1 hour to prepare a reaction solution.
[0091] At least XX ml of ether was added to the reaction solution to generate a precipitate, which was collected by filtration and washed with ether, acetone, and methanol in a cycle for several times, filtered, and dried in vacuo at 37° C. to obtain phosphorylated chitosan for later use.
[0092] Graphite coating with surfactants:
[0093] The graphite was ball milled for 12 h with the rotation speed controlled at 200 r / min.
[0094] An aqueous solution containing 0.2 wt% of LAS was mixed with ethanol at a volume ratio of 9:1 to form a mixed solution, and ball-milled graphite particles were added while stirring. After stirring for a period of time, the graphite was filtered out and dried to obtain surfactant-coated graphite.
[0095] Comparative Example 1
[0096] Negative electrode preparation:
[0097] Graphite: carbon black conductive agent: sodium carboxymethyl cellulose / styrene-butadiene rubber are mixed in a mass ratio of 8:1:1 and diluted with water to obtain a negative electrode slurry. After magnetic stirring for 6 hours, the negative electrode slurry is coated on copper foil and dried to make a lithium-ion battery negative electrode sheet. The required negative electrode sheet is obtained by rolling and slicing. The thickness of the negative electrode sheet is 100 microns.
[0098] Assembling lithium-ion batteries:
[0099] The battery is assembled by combining metallic lithium with the negative electrode of lithium-ion battery and using polypropylene microporous membrane as separator. The electrolyte of the battery is 1 mol·L -1 The LiPF6 was used as the electrolyte salt and dissolved in a solution of EC:DMC:EMC mixed in a volume ratio of 1:1:1.
[0100] test:
[0101] The lithium-ion battery was subjected to constant current charge and discharge tests at current densities of 0.1C, 0.2C, 0.5C, 1C, and 5C, respectively. The battery test temperature was generally around room temperature (25°C).
[0102] Comparative Example 2
[0103] Negative electrode preparation:
[0104] Graphite @LAS: carbon black conductive agent: sodium carboxymethyl cellulose / styrene-butadiene rubber were mixed in a mass ratio of 8:1:1 and diluted with water to obtain a negative electrode slurry. The subsequent preparation process of the lithium ion battery negative electrode sheet, the lithium ion battery assembly steps and the testing method were the same as those in Comparative Example 1.
[0105] Example 3
[0106] 100 mg of phosphorylated chitosan was dissolved in 10 ml of water to prepare a phosphorylated chitosan aqueous solution.
[0107] 0.8 g of graphite and 0.1 g of carbon black conductive agent were weighed and added to the above-mentioned phosphorylated chitosan aqueous solution and stirred to obtain a negative electrode slurry, which was then coated on a copper foil and dried.
[0108] The subsequent preparation of the lithium-ion battery negative electrode sheet, lithium-ion battery assembly and lithium-ion battery testing methods are the same as those in Comparative Example 1.
[0109] The constant current charge and discharge test is carried out at a current density of 0.1C, and the battery test temperature is generally around room temperature 25°C.
[0110] See also Figure 2The battery constant current charge and discharge test shows that the first discharge capacity is 341mAh g -1 After 50 cycles, the specific capacity is 342.6 mAh g -1 After 100 cycles, the specific capacity is 341.4 mAh g -1 , the battery discharge capacity has basically not decayed.
[0111] Compared with the test results of Comparative Example 1 at a current density of 0.1C, the discharge specific capacity and cycle stability of the lithium ion battery using phosphorylated chitosan as a binder are improved, and the electrochemical performance of the lithium ion battery is improved.
[0112] Example 4
[0113] 100 mg of phosphorylated chitosan was dissolved in 10 ml of water to prepare a phosphorylated chitosan aqueous solution.
[0114] 0.8 g of graphite@LAS and 0.1 g of carbon black conductive agent were weighed and added to the above-mentioned phosphorylated chitosan aqueous solution and stirred to obtain a negative electrode slurry, which was then coated on a copper foil and dried.
[0115] The subsequent preparation of the lithium-ion battery negative electrode sheet, lithium-ion battery assembly and lithium-ion battery testing methods are the same as those in Example 3.
[0116] See also Figure 3 The battery constant current charge and discharge test shows that the first discharge capacity is 364mAh g -1 After 50 cycles, the specific capacity is 361.3 mAh g -1 , the specific capacity after 0 cycles is 360mAh g -1 .
[0117] When graphite@LAS is used to replace the negative electrode graphite, the discharge capacity of the battery is improved to a certain extent. Compared with the test results of Comparative Example 2 at a current density of 0.1C, the cycle stability of the lithium-ion battery with phosphorylated chitosan as the binder is higher than that of the traditional sodium carboxymethyl cellulose / styrene-butadiene rubber binder, and the electrochemical stability of the battery is improved.
[0118] Phosphated chitosan is evenly dispersed in the negative electrode material as a binder, and its negatively charged adsorption on the surface of graphite@LAS enables the phosphorylated chitosan coated on the surface of graphite@LAS particles to better resist the stress caused by the volume expansion of the active material during lithium insertion, thereby improving the battery cycle performance. On the other hand, phosphorylated chitosan plays a role in adsorbing lithium ions and further promotes the formation and stability of the SEI film.
[0119] Example 5
[0120] 50 mg of phosphorylated chitosan was dissolved in 10 ml of water to prepare a phosphorylated chitosan aqueous solution.
[0121] The other material components and amounts are the same as those in Example 4, and the subsequent lithium-ion battery negative electrode sheet preparation, lithium-ion battery assembly, and lithium-ion battery testing methods are the same as those in Example 3.
[0122] Example 6
[0123] 100 mg of phosphorylated chitosan was dissolved in 10 ml of water to prepare a phosphorylated chitosan aqueous solution.
[0124] The other material components and amounts are the same as those in Example 4, and the subsequent lithium-ion battery negative electrode sheet preparation, lithium-ion battery assembly, and lithium-ion battery testing methods are the same as those in Example 3.
[0125] Example 7
[0126] 150 mg of phosphorylated chitosan was dissolved in 10 ml of water to prepare a phosphorylated chitosan aqueous solution.
[0127] The other material components and amounts are the same as those in Example 4, and the subsequent lithium-ion battery negative electrode sheet preparation, lithium-ion battery assembly, and lithium-ion battery testing methods are the same as those in Example 3.
[0128] See also Figure 4 , Figure 4 4 is a comparison chart of test data of the lithium-ion batteries of Example 5, Example 6 and Example 7.
[0129] The data corresponding to Example 6 show better cycle performance. From the comparison of the data of Example 5 and Example 6, it can be seen that increasing the amount of phosphorylated chitosan within a certain range will increase the density of multi-electron groups on the surface of the negative electrode, that is, increase the adsorption active sites on the negative electrode surface, which is beneficial to the adsorption of lithium ions and promotes the formation and stabilization of the SEI film on the negative electrode surface.
[0130] In addition, it can be seen from the comparison of the data of Example 6 and Example 7 that, since phosphorylated chitosan itself is a non-conductive substance, unlimited increase will lead to an increase in electrode resistance, thereby affecting the battery cycle performance.
[0131] Example 8
[0132] 100 mg of phosphorylated chitosan was dissolved in 10 ml of water to prepare a phosphorylated chitosan aqueous solution.
[0133] 0.8 g of graphite@LAS and 0.1 g of carbon black conductive agent were weighed and added to the above-mentioned phosphorylated chitosan aqueous solution, stirred to obtain a negative electrode slurry, coated on a copper foil and dried.
[0134] The subsequent preparation of the lithium-ion battery negative electrode sheet, lithium-ion battery assembly and lithium-ion battery testing methods are the same as those in Example 4.
[0135] Constant current charge and discharge tests were carried out at current densities of 0.1C, 0.2C, 0.5C, 1C, and 5C, respectively. The battery test temperature was generally around room temperature (25°C).
[0136] See also Figure 5 As the discharge rate increases, the capacity of the negative electrode using phosphorylated chitosan combined with graphite @ LAS decays slowly. When the rate increases to 5C, the capacity decreases by 12.9% relative to the rate of 0.1C.
[0137] Compared with Comparative Example 2, which uses a combination of sodium carboxymethyl cellulose / styrene-butadiene rubber and graphite@LAS, the negative electrode capacity of Comparative Example 2 decays relatively quickly. When the rate increases to 5C, the capacity decreases by 24.4% relative to the rate of 0.1C.
[0138] Therefore, it is further confirmed that the combination of phosphorylated chitosan and graphite@LAS can better resist the stress caused by the volume expansion of the active material during lithium insertion, thereby improving the battery cycle performance.
[0139] Comparison and analysis between the comparative examples and the examples above demonstrate that the use of phosphorylated chitosan as a binder adsorbs lithium ions, further promoting the formation and stabilization of the SEI film, effectively improving the specific discharge capacity and cycling stability of the lithium-ion battery. Furthermore, the combination of surface-pretreated graphite and phosphorylated chitosan allows for mutual adsorption and hydrogen bonding, enabling the phosphorylated chitosan to better resist the stress caused by the volume expansion of the active material during lithium insertion, thereby effectively improving the battery's cycling performance.
[0140] The above-described embodiments merely illustrate several implementations of the present invention, and while their descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, all of which fall within the scope of protection of the present invention. Therefore, the scope of protection of the present invention shall be determined by the appended claims.
Claims
1. A negative electrode material, characterized in that: The invention comprises graphite, a carbon black conductive agent and phosphorylated chitosan, wherein the graphite is coated with a surfactant, the mass ratio of the graphite coated with the surfactant, the carbon black conductive agent and the phosphorylated chitosan is 8:1:1, and the surfactant is selected from one of sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide and sodium dodecyl sulfate.
2. A negative electrode sheet for a lithium-ion battery, characterized in that: It comprises a copper foil and the negative electrode material according to claim 1 coated on the surface of the copper foil.
3. A method for preparing a negative electrode sheet for a lithium ion battery, characterized in that: The method comprises the following steps: coating graphite with a surfactant, wherein the surfactant is selected from one of sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide and sodium dodecyl sulfate; mixing the graphite coated with the surfactant, a carbon black conductive agent and phosphorylated chitosan in a mass ratio of 8:1:1 and stirring with water to obtain a negative electrode slurry; and coating the negative electrode slurry on a surface of a copper foil and drying.
4. The method for preparing a negative electrode sheet for a lithium ion battery according to claim 3, characterized in that: The step of coating graphite with a surfactant is specifically as follows: mixing an aqueous solution containing 0.2wt% of the surfactant with anhydrous ethanol in a volume ratio of 9:1 to form a mixed solution; placing the graphite in the mixed solution and stirring for 60 to 120 minutes, filtering, and drying.
5. The method for preparing a negative electrode sheet for a lithium ion battery according to claim 4, characterized in that: Before the graphite is put into the mixed solution, the method further comprises the step of ball milling the graphite for 12 to 13 hours.
6. The method for preparing a negative electrode sheet for a lithium ion battery according to claim 3, characterized in that: The phosphorylated chitosan is prepared according to the following steps: dissolving chitosan in methanesulfonic acid, gradually adding P2O5 at 10-15°C and stirring for 1h to obtain a reaction solution; adding ether to the reaction solution to generate a precipitate; washing the precipitate and drying it to obtain the phosphorylated chitosan.
7. The method for preparing a negative electrode sheet for a lithium ion battery according to claim 6, characterized in that: The mass ratio of the chitosan to the P2O5 is 1:2-3, and the solid-liquid ratio of the chitosan to the methanesulfonic acid is 1g:7ml.
Citation Information
Patent Citations
Chitosan phosphorylation modification method
CN103224574A
Surface-modified graphite negative electrode material, and preparation method and application thereof
CN103311521A
Additive for lithium-sulfur batteries and anode material containing same
CN103515613A
Preparation method of positive plate of lithium sulphur secondary battery
CN103682255A
Method for processing surface of natural griaphite for lithium ion battery
CN1599102A